2017
DOI: 10.1002/nbm.3720
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive evaluation of renal pH homeostasis after ischemia reperfusion injury by CEST‐MRI

Abstract: Acute kidney injury (AKI) in mice caused by sustained ischemia followed by reperfusion is associated with acute tubular necrosis and renal dysfunctional blood flow. Although the principal role of the kidney is the maintenance of acid-base balance, current imaging approaches are unable to assess this important parameter, and clinical biomarkers are not robust enough in evaluating the severity of kidney damage. Therefore, novel noninvasive imaging approaches are needed to assess the acid-base homeostasis in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 55 publications
4
45
0
Order By: Relevance
“…Their first application as pH CEST-MRI agents involved the use of iopamidol (Isovue R , Bracco Diagnostic), possessing two amide proton pools that can be saturated at 4.2 and 5.5 ppm (91,92). The set-up of a ratiometric procedure allows to accurately measure extracellular tissue pH (pHe) in the pH range of 5.5-7.9, independently of the contrast agent concentration, with an accuracy of 0.1 units at several magnetic fields (93)(94)(95). CEST-MRI tumor pH imaging was combined to FDG-PET to elucidate the deregulation of tumor metabolism in a breast cancer model (96).…”
Section: Extracellular Tumor Ph Imagingmentioning
confidence: 99%
“…Their first application as pH CEST-MRI agents involved the use of iopamidol (Isovue R , Bracco Diagnostic), possessing two amide proton pools that can be saturated at 4.2 and 5.5 ppm (91,92). The set-up of a ratiometric procedure allows to accurately measure extracellular tissue pH (pHe) in the pH range of 5.5-7.9, independently of the contrast agent concentration, with an accuracy of 0.1 units at several magnetic fields (93)(94)(95). CEST-MRI tumor pH imaging was combined to FDG-PET to elucidate the deregulation of tumor metabolism in a breast cancer model (96).…”
Section: Extracellular Tumor Ph Imagingmentioning
confidence: 99%
“…MRI‐chemical exchange saturation transfer (CEST) pH imaging can be used to evaluate renal ischemia reperfusion injury. In mouse models, it distinguishes the evolution from moderate to severe AKI, with subsequent restoration of normal pH values serving as an indicator for renal recovery . Arterial spin labeling perfusion MRI also accurately assesses cortical and medullary malperfusion in the setting of AKI, but the relationship between arterial spin labeling measurements and renal recovery could not be quantified .…”
Section: Cut‐off Criteria Used In Clinical Trialsmentioning
confidence: 99%
“…In particular, the average pH increased from 6.7 to 7.3 at 3 days after injury, but returned back to 6.7 at 21 days of glycerol administration. This same group showed that pH changes associated with AKI caused by sustained ischemia followed by reperfusion can be detected in a unilateral injury model (one kidney injured) . In this second study, both moderate (20 min) and severe (40 min) injuries were induced through clamp occlusion, which were imaged at several time points thereafter (Days 0, 1, 2, 7).…”
Section: Cest Mri Ph Imaging Applicationsmentioning
confidence: 99%
“…(d), (f), representative MRI‐CEST pH maps over imposed onto anatomical images before and after moderate (d), and severe (f), AKI at different time points (day 1, day 2, and day 7) showing pronounced alkalinazation and reduced filtration (non‐colored pixels within the renal region) of the pH‐responsive contrast agent in clamped kidney in comparison to contralateral kidney. Reproduced from:…”
Section: Cest Mri Ph Imaging Applicationsmentioning
confidence: 99%